Kompetensi pustakawan dalam publikasi karya tulis ilmiah di Forum Perpustakaan Perguruan Tinggi Muhammadiyah ‘Aisyiyah - Pujiastuti, Ana; Zulaikha, Sri Rohyanti (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. Efforts made to increase the competencies of librarians can be made through the publication of scientific writing. The research aims to determine the competence of librarians in the publication of scientific writing at the Muhammadiyah 'Aisyiyah Higher Education Library Forum Regional Coordinator for the Special Region of Yogyakarta-South Central Java (FPPTMA Regional Coordinator DIY-South Java). Research methods. This study used a qualitative method, with informants 15 people with snowball sampling. Data collection used observation, in-depth interviews, and documentation. Data analysis techniques use data condensation, data presentation, and drawing conclusions. To test the validity of the data, we used triangulation techniques. Results and Discussion. Librarians' ability to publish scientific writing is based on their competencies in motive, character, self-concept, knowledge, and skills. The impact of scientific writing publication competency encourages librarians to be productive in producing scientific writing publications which will increase librarian branding. Conclusion and recommendations. Librarians who have consistent character will produce quality scientific writing. It cannot be separated from communication skills and mastery of scientific writing techniques. This research suggests establishing a regular writing program that can facilitate librarians in their work.